End-to-end security enabled intelligent remote IoT monitoring system - Saleem, Kashif; Zinou, Mohammed Farouk; Mohammad, Farah; Ouni, Ridha; Elhendi, Ahmed Zohier; Almuhtadi, Jalal (Frontiers in Physics, 2024)
Internet of things (IoT) compose of million of devices connected together over the internet.IoT plays a vital role now a days and especially in future, the most of the monitoring and data collection. The data should be secure while collection and as well in the process of transferring till the destination whether Service Organization Control (SOC) or to cloud for storage. In this paper, a secure IoT based intelligent monitoring system is proposed. The Waspmote platform is utilized to build an intelligent IoT station that communicates over cellular communication for transferring data to the cloud. The algorithm is injected to automatically filter and only keep the new data for transfer to avoid redundancy. The IoT monitoring station is enabled with an advanced encryption standard (AES) 256-bit algorithm for onboard data encryption and transfer cipher text. This helps in securing the proposed monitoring system from brute force, man in the middle, phishing, spoofing, and denial of service (DoS) attacks. The encrypted data is then stored over the cloud to ensure privacy. Moreover, the mobile application (mApp) is developed to be installed on handheld devices for calling the secure data from the cloud, decrypting it, and displaying it as per user input, whether real-time or historical. The experimental results demonstrate the complexity evaluation and reliability of IoT monitoring systems with end-to-end data security in terms of encryption algorithm delay and data rate, respectively.